Withdrawal time as a quality indicator for colonoscopy – a nationwide analysis - Moritz, V.; Bretthauer, M.; Ruud, H. K.; Glomsaker, T.; de Lange, T.; Sandvei, P.; Huppertz-Hauss, G.; Kjellevold, Ø.; Hoff, G. (Endoscopy, 2012)
Background and study aims: A withdrawal time of at least 6 min has been recommended as a quality indicator for colonoscopy. One drawback of many of the studies that have investigated withdrawal time and produced conflicting results has been their single-center design involving few endoscopists. Therefore, the validity of withdrawal time as a quality measure remains unclear. This study explores the value of individual withdrawal time in a nationwide analysis.Patients and methods: This prospective cohort study comprised data from outpatient colonoscopies performed at 19 Norwegian centers from January to September 2009 and registered in the Norwegian Gastronet Quality Assurance (QA) program. The participating endoscopists were characterized by their median withdrawal time for visual colonoscopies (diagnostic colonoscopies without biopsy or therapy) and categorized into two visual withdrawal time (VWT) groups (< 6 min or ≥ 6 min) to analyze the predictive value of VWT for detection of one or more polyps ≥ 5 mm in diameter using multiple logistic regression models.Results: The study included 4429 consecutive colonoscopies performed by 67 endoscopists. The adjusted odds ratio for the detection of polyps ≥ 5 mm was 1.21 (95 %CI 0.94 – 1.56, P = 0.14) for endoscopists with a median VWT ≥ 6 min compared with endoscopists with a median VWT < 6 min.Conclusion: Withdrawal time using 6 min as the threshold is not a strong predictor of the likelihood of finding a polyp during colonoscopy and should not be used as a quality indicator.